A Production and operations management study on Universal Robina Corporation - Difuntorum, Lee Michael (College of Engineering, 2001)
This is a study on Universal Robina Corporation (URC) which is a pioneer in the Philippine snack-food industry. This paper will focus on the Choco Pretzels 100s product manufactured in the URC Canlubang, Laguna Plant. The objective of the researchers is o document the existing system, find improvement opportunities, and to come up with sound recommendations using tools in Production and Operations Management. The group used direct observations, interviews with key production and operations personnel, and examined company records to acquire relevant data on the Choco Pretzels 100s operations. The group focused on three production areas. First is the issue of conflicting production plans, wherein the managers obtained production plans from URC Headquarters (called General Distribution or GD plans) and another from the URC Warehouse Group (called the Distribution Requirement Plan or DRP). The group recommends that the Production Managers come up with a forecast of their own, eliminating the need to be fully dependent on the soon-to-be-phased-out GD plan and the frequently delayed DRP plans. The forecasting method proposed is the exponential smoothing forecasting method, obtained through analysis of production figures in the last two years. The Choco Pretzels 100s operations lack a systematic aggregate plan, and this leads to problems in workforce management and machine/equipment maintenance. The group recommends a plan that smoothens out the monthly production output. A level weekly production plan eliminates the need to increase the production load in the last few days of the month, which is the present business practice. The quality of the goods will be a minor issue since pullout of the choco pretzels is done frequently. The third issue deals with inventory management woes. The Production and Operations Manager of the Choco Pretzels 100s lack information on the capacity of the currently disorganized staging area. This problem is made worse due to the highly fluctuating monthly and daily production pullouts. The group found the inventory level capacity in the staging area, and recommends a system that will aide the managers and line operators in inventory management. The group recommends that the URC Canlubang Choco Pretzels management team adopt the said proposals, Ultimately, the foremost objective of this paper is that the recommendations will be beneficial to the company.